Exploring the evolution of endocrowns: a bibliometric analysis (2010-2024) - Nair, Sanjana Jayakumar; Azhuvancheri, Jinesh; Gupta, Saurabh Kumar; Krishnan, Gopika (International Journal of Research in Medical Sciences, 2025)
The aim of this bibliometric analysis is to evaluate the global research trends and patterns in publications related to endocrowns, a conservative restorative option for endodontically treated teeth. Endocrowns have gained significant attention due to their ability to preserve tooth structure while providing adequate retention and aesthetics. This study analyzed the scientific output from various databases, including Scopus, Web of Science, and PubMed, focusing on publication trends, geographic distribution, most cited articles, prolific authors, and key journals publishing on the topic. A systematic search was performed using specific keywords such as "endocrown," "endodontically treated teeth," and "ceramic restorations." The data was then processed using bibliometric software to visualize collaborations, citation networks, and emerging trends in the field. Results show a steady increase in publications over the last decade, with notable contributions from Europe and Asia. The top-cited articles primarily discuss clinical outcomes, material choices, and long-term success rates of endocrowns. This analysis highlights the growing interest in endocrowns as a restorative solution and provides insights into future research directions, including advances in materials science and long-term clinical performance. The findings of this study serve as a comprehensive guide for researchers, clinicians, and academicians in understanding the evolution and current state of research on endocrowns.